KAJIAN STRES HOSPITALISASI TERHADAP PEMENUHAN POLA TIDUR ANAK USIA PRASEKOLAH DI RUANG ANAK RS BAPTIS KEDIRI - Wahyuningsih, Aries; Febriana, Desita (Jurnal Penelitian STIKES Kediri, 2011)
abstract backgorund : Hosptalized stress is a process which causes a reason that obliging child to stay temporarly in the hospital, experiencing therapy and treatment until discharge instruction to return back home. Hospitalized stress can cause the child experience impairment of sleep pattern, especially pre school children. The negative impact from hospitalized stress to pre school children including physical disorder, psychological disorder, social and adaptation disorders towards environment. Most problem which is often complained was the difficulty to minimize child’s sleep in improving freedom on their bed. Method : The design used in this study was linear regression. The population was all parents with pre school children who stayed in pediatric ward. The samples were 30 respondents who met criteriaa inclusion using total sampling. The independent variable was hospitalized stress and the dependent variable was disorder of sleep pattern, the data was collected using questionnaire and interview, then analyzed using linear regression with significantt level α ≤ 0,05. Conclusion : The result of this study showed that respondents had moderate hospitalized stress, they were 24 respondents (85,4%). More that 50% respondents had worse sleep pattern, they were 23 respondents (62%). The result of statistical test using linear regression was p = 0,035, it meant ho was refused and ha was accepted. Key words : Stretching, Joint Pain, and the Elderly